RANCANG BANGUN APLIKASI PENILAIAN UJIAN PRAKTIK SIM (SURAT IZIN MENGEMUDI) C BERBASIS ARDUINO MEGA2560 - Siahaan, Aron Octavianus; Harianto, Harianto; Susanto, Pauladie (Journal of Control and Network Systems (JCONES), 2017)
Driving License is proof of registration and identification provided by the POLRI to a rider who has met the requirements. This time the author will focus on practice exams procedures of C driving license, where graduated or not the applicant of C driving license depends on his skill on driving a motor vehicle while passing through the barriers that are provided. At this time the process of making C driving license is always maintained and assessed by several officers. Therefore, the author will make the assessment system of C driving license practice exams that have been computerized. Value capturing is based on the stability of the vehicle speed and the number of times an applicant to touch / hit the road divider peg that has been determined. Then the breach data of the driving license applicant will be sent to officer’s computer that is shown on application created with Microsoft Visual Basic 6.0. Based on the results of the final test on this research, the application of practice exams assessment succeeded to detect violations on the peg / barrier pole trajectory, the application successfully measures the speed of the vehicle as it passed and applications can save participants’ data.